Shell occupancy of the intertidal hermit crab Clibanarius erythropus (Decapoda, Diogenidae) on São Miguel (Azores). - Botelho, Andrea Z. (2000)
The intertidal hermit crab Clibanarius erythropus was collected at three sites on São Miguel (Azores) during low spring tides. Shells occupied were identified and measured. Crab sizes ranged from 1.78 to 13.67 mm (cephalothoracic shield length), with an average size of 4.40 +- 1.44 mm. Of the 19 different shells utilised, the most frequent were Littorina striata (23.8%), Nassarius incrassatus (22.5%) and Mitra sp. (22.0%). At Fenais da Luz. L. strita was most frequently occupied, while at Água de Alto it was N. incrassatus and, at Caloura, Mitra sp. shells were most frequently used. Shell selection appears to be determined by respective sizes of hermit crab and shell species. Small size-class crabs occupy more shell species than larger crabs. The smallest crab was found at Fenais da Luz occupying a small Bittium sp., whereas the largest crab was found at Caloura inhabiting Stramonita haemastoma.